2013
DOI: 10.1007/s10973-013-3087-2
|View full text |Cite
|
Sign up to set email alerts
|

Melting and crystallization DSC profiles of milk fat depending on selected factors

Abstract: The aim of this study was to test selected factors, such as sample preparation and measurement procedure, potentially influencing repeatability of DSC analysis of milk fat melting and crystallization. The study investigated the effect of such factors as scanning rate, type of sample pans, method of butter dehydration, and final temperature in the cooling experiment. Based on recorded results, it was observed that cooling rate has a considerable effect on temperature, enthalpy, and height of peaks in the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 20 publications
7
30
0
1
Order By: Relevance
“…; Covas et al . ; Stevenson and Hurst ; Tomaszewska‐Gras ). Rich sources of phenolic compounds are commonly consumed as beverages like coffee, tea, and herb infusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Covas et al . ; Stevenson and Hurst ; Tomaszewska‐Gras ). Rich sources of phenolic compounds are commonly consumed as beverages like coffee, tea, and herb infusions.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are compounds widespread in the plant kingdom that are widely studied due to their positive activity in humans. Benefits from the consumption of polyphenols include a reduced risk of cancer, cardiovascular disease, neurodegeneration, diabetes, and osteoporosis (Fortes et al 2003;Hao and He 2004;Arts and Hollman 2005;Graf et al 2005;Manach et al 2005;Scalbert et al 2005;Covas et al 2006;Stevenson and Hurst 2007;Tomaszewska-Gras 2013). Rich sources of phenolic compounds are commonly consumed as beverages like coffee, tea, and herb infusions.…”
Section: Introductionmentioning
confidence: 99%
“…Lambelet and Ganguli [13] reported that measurements based on crystallization diagrams have the advantage of avoiding problems linked to polymorphism of fats, so that the results are independent of the thermal treatment of the samples prior to analysis. However, it was shown by the study on milk fat [16] that melting curves are characterized by better reproducibility than crystallization curves, only if the sample is initially heated to destroy any previous crystalline structure. There is also little research regarding the comparison of the feasibility of DSC crystallization and melting curves for monitoring the presence of nonmilk fats.…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of DSC applicability, it is crucial to identify the factors affecting measurement repeatability. The factors connected with sample preparation and conditions of DSC analysis (heating and cooling rates) were analyzed by Tomaszewska-Gras (2013). Heterogeneous organic substances with a complex composition such as food are characterized by the natural variability of raw material, which should also be considered.…”
Section: Introductionmentioning
confidence: 99%